Connecting research and community: a methodological framework for investigating CMV transmission in childcare settings - Del’Olio, Karen; Geiger, Annie; Terry, Judith; Callaghan, Cindi; Howe, Lauren; Hamel, Cheryl; Platia, Delaney; Blake, Alyssa; Tran, Lisa; Davenport, Anne; Orvek, Elizabeth; Lammi, Stephen; et al. (Frontiers in Pediatrics, 2025)
The CMV Transmission and Immune Tracking (TransmIT) Study was developed to address critical gaps in understanding of cytomegalovirus (CMV) transmission dynamics in early education and care (EEC) settings. This two-stage, community-engaged study design integrates EEC center partnerships, digital study platforms, and data pipeline infrastructures to enable longitudinal virologic and immunologic surveillance in this high-exposure environment. Stage I focused on establishing foundational components of the study, including a geographically diverse EEC center network, culturally tailored recruitment strategies, a community advisory board, protocols for participant enrollment and saliva sample collection, and optimized laboratory assays to measure viral shedding in saliva. The study approach honed during Stage I is intended to support future longitudinal investigations into viral shedding patterns, immune responses, and co-infections among children and staff in EEC centers. This manuscript presents a methodological framework for conducting community-centered scalable research in early childhood settings with relevance for CMV and other infectious diseases of public health importance.